Key data elements for a successful pediatric rheumatology virtual visit: a survey within the PR-COIN network - Goh, Y. Ingrid; Ryan, Meghan E.; Akoghlanian, Shoghik; Pooni, Rajdeep; Harris, Julia G.; Bullock, Danielle R.; Vora, Sheetal S.; Lee, Tzielan C.; Tse, Shirley M.L.; Barbar-Smiley, Fatima (Frontiers in Pediatrics, 2024)
Juvenile idiopathic arthritis (JIA) is the most common childhood rheumatic disease which is commonly monitored by a combination of history, physical examination, bloodwork, and imaging. The COVID-19 pandemic prompted a rapid shift to telemedicine to ensure that patients continued to receive healthcare. The shift to telemedicine changed the methodology and ability of healthcare providers to monitor their patients' progress, as they were unable to perform direct hands-on assessments.The following survey sought to understand the impact of switching pediatric rheumatology healthcare delivery from in-person to telemedicine modality. Specifically, it sought to examine the rate of collection of critical data elements (CDE) for monitoring JIA disease activity and outcomes, barriers and facilitators to its collection, opinions on difficulty and importance of collecting CDE over telemedicine, tools and electronic medical record modifications that facilitated CDE collection, and other data elements that were important to collect during telemedicine visits.A cross-sectional survey was sent to healthcare provider at all PR-COIN centers who saw patients using telemedicine. Qualitative data was analyzed using descriptive statistics and qualitative data was analyzed using an inductive approach.Survey respondents reported that they documented the CDE at least 75% of the time. Barriers to assessing and documenting critical data elements included 1) the inability to palpate or visualize all joints over telemedicine, 2) connectivity issues, and 3) forgetfulness with collecting all critical data elements. Respondents suggested using reminders within the electronic medical record to prompt documentation completeness and improve reliability. They also suggested including medication adherence, quality of life, and patient/caregiver satisfaction with their telemedicine experience as part of their documentation.A few centers reported that they had established processes to assist with data collection in advance of the telemedicine visit; however, the variation in responses reflects the need to standardize the process of providing care over telemedicine.Multiple barriers and facilitators to collecting CDE during telemedicine visits exist. Given that a proportion of the population will continue to be seen over telemedicine, teams need to adapt their practices to consistently provide high-quality care over virtual platforms, ensuring that patients at any institution receive a standardized level of service.